UJI KUALITAS DEDAK PADI YANG DISIMPAN DENGAN ARANG KAYU DAN ARANG BATOK KELAPA PADA MASA SIMPAN 6 MINGGU - Rismars Hizkia; Farida Fathul; Liman . (JURNAL ILMIAH PETERNAKAN TERPADU, 2013)
The potency of rice bran which could be used as the cattle fare in 2011 was + 6,539 billion ton. The problem in using rice bran as fare product was the low stability because of hydrolysis and oxidation rancidity. The hydrolysis and oxidation rancidity was happened during the saving could spoil the quality of the rice bran, especially the lipid contents. The one of the way which could be used to avoid the process of hydrolysis and lipid oxidation in rice bran was by adding the charcoal. The charcoal contents carbon which could adsorb H2O and its pores could tie O2 molecule. This research was purposed (1) to know the influence of using wood charcoal and coconut shell charcoal toward the quality of rice bran which was saved in 6 weeks; (2) to know which one was the best treatment based on the physical characteristic and chemichal composition of rice bran which was in storage with wood charcoal and coconut shell charcoal in 6 weeks. The scheme of the experiment in this research was used random complete experiment with 3 treatments, each treatment was repeated 4 times. If the result of varian analysis was obviously influenced at one variety, so the next experiment would be done with the least obvious different experiment at obvious level 5% and 1%. The result of this research showed that the use of wood charcoal and coconut shell charcoal obviously influence (P<5%) toward the smell and water proportion and very obviously influence (P<1%) toward the number of rice bran peroxida which was in a storage in 6 weeks. Coconut shell charcoal was the best media in rice bran saving in 6 weeks because it produced the smell that was not rancid and the lowest peroxida number (6,39 + 0,07 meq/kg). Key Word: rancidity, rice bran, charcoal adsorbtion